AMPK and Polycystic Kidney Disease Drug Development: An Interesting Off-Target Target - Caplan, Michael J. (Frontiers in Medicine, 2022)
Autosomal Dominant Polycystic Kidney Disease is a genetic disease that causes dramatic perturbations of both renal tissue architecture and of a multitude of cellular signaling pathways. The relationship between the products of the genes whose mutations cause polycystic kidney disease and these signaling pathways remains difficult to determine. It is clear, however, that cellular metabolism is dramatically altered in cells that are affected by polycystic kidney disease mutations. Adenosine monophosphate-stimulated protein kinase is a master regulator of cellular energy use and generation pathways whose activity appears to be perturbed in cells affected by polycystic kidney disease. Furthermore, modulation of this enzyme’s activity may constitute a promising approach for the development of new therapeutics for polycystic kidney disease.